INTELLECTUAL ACTIVITY IN CITIZENSHIP - Meish, Alla; Grechana, Karina (Sworld-Us Conference proceedings, 2024)
In today's world, where information flows in a river and challenges become more and more complex, the intellectual activity of citizens turns into not just a fashionable trend, but a key factor that determines the development of society, its stability and